Local Demand, Quality of Place, and Urban Tourism Competitiveness - Weng, Jin; Xiao, Jiaying; Yu, Larry (Frontiers in Psychology, 2022)
Most studies on tourism destination competitiveness examined the direct relationships of destination attributes and destination competitiveness. Few studies explored the intervening mechanisms between destination attributes and competitiveness. This study selected cities above the “alpha” level in the Globalization and World Cities Research Network rankings as samples to examine the relationship between local demand and urban tourism competitiveness mediated by the quality of place. Results showed that the relationship between urban wealth and tourist arrivals was completely mediated by the quality of place, while the mediating effect was not significant in the relationship between urban wealth and per capita tourism spending, though per capita tourism spending was directly and positively associated with urban wealth. In other words, richer cities had a higher quality of place, and a higher quality of place attracted more tourists but did not increase tourism per capita spending. Furthermore, the study found that there were two opposite influence paths of city size on urban tourism competitiveness. Although urban tourism competitiveness was directly and positively affected by population, the population had a significant negative effect on urban tourism competitiveness mediated by the quality of place. Through the quality of place, we can be aware of the indirect negative effect suppressed by the direct positive effect. This study revealed that the quality of place helped to better understand the competitiveness of urban tourism.